2022
DOI: 10.52208/klasikal.v4i2.279
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Climate in the Context of Teaching Practices in Junior High Schools

Abstract: ABSTRACT This study explores the teaching practices in junior high schools in Maros Regency, South Sulawesi Province, Indonesia that promote the development of a positive classroom climate. Interviews were used to gather the data. Twenty-four class-teachers from 12 junior high schools participated in individual semi structured interviews. The data collected from teacher interviews were analysed using NVivo version 10. The qualitative analysis revealed that two main teaching practices influenced cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Through a seating arrangement, lower learners can directly benefit from having smarter learners seated next to them. This proximity lets them ask questions and request assistance directly, thereby enhancing their comprehension of the subject matter (Abdelrahman & Wang, 2023;Abdul Maing & Mahmud, 2022) The participants revealed that the seating arrangements in their speaking class comprise round table, par pods, and group pods. They stated that sitting in groups provides learners with the chance to engage in direct interaction with their peers.…”
Section: Speaking Correction Techniquesmentioning
confidence: 99%
“…Through a seating arrangement, lower learners can directly benefit from having smarter learners seated next to them. This proximity lets them ask questions and request assistance directly, thereby enhancing their comprehension of the subject matter (Abdelrahman & Wang, 2023;Abdul Maing & Mahmud, 2022) The participants revealed that the seating arrangements in their speaking class comprise round table, par pods, and group pods. They stated that sitting in groups provides learners with the chance to engage in direct interaction with their peers.…”
Section: Speaking Correction Techniquesmentioning
confidence: 99%
“…The CMS has been used as a measure of students' classroom experiences in independent studies, assessing the technical properties of the CMS in English and as translated into Chinese, Indonesian, and Urdu [20][21][22][23]. Factor analytic studies have confirmed that the items loaded consistently onto their assigned scale for both English and translated measures.…”
Section: The Classmaps Surveymentioning
confidence: 99%